Re-examining the health effects of radiation and its protection. (9th June 2006) - Luan, Y.C.; Shieh, M.C.; Chen, S.T.; Kung, H.T.; Soong, K.L.; Yeh, Y.C.; Chou, T.S.; Fang, W.C.; Yao, S.L.; Pong, C.J.; Mong, S.H.; Wu, J.T.; et al.
The health effects of radiation from atomic explosions in Japan were completely different from those due to radiation from the Co-60 contaminated apartments in Taiwan. The sudden exposure to acute radiation in extremely high doses killed Japanese people, and harmed the survivors in lower doses as shown by increased cancer mortality, especially the leukemia based on the LNT model. The chronic radiation received by the residents unknowingly in the Co-60 contaminated apartments in Taiwan, even in higher doses, caused no excess cancer deaths; on the contrary their spontaneous cancer deaths were sharply reduced to only about 2.5% of that of the general population, and hereditary defects in their offspring were only 5%–7% of those of the normal population. Therefore, the residents in the Co-60 contamination apartments had coincidently accomplished a human experiment of the health effects to human beings. The chronic radiation received from the Co-60 contaminated houses is quite similar to the radiation exposure to the workers and public in the peaceful use of nuclear energy and medical radiation. Acute radiation from a nuclear accident could harm a limited number of people, but the chronic radiation might benefit people, such as in the case of the Chernobyl accident. People should not be fearful of chronic exposure to low radiation and the traditional radiation protection policy and practices used in past 60 years should be revised based on the health effects observed in Taiwan.